2019
DOI: 10.48550/arxiv.1903.11247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Hierarchical Collapse In Molecular Clouds. Towards a Comprehensive Scenario

Enrique Vázquez-Semadeni,
Aina Palau,
Javier Ballesteros-Paredes
et al.

Abstract: We present a unified description of the scenario of global hierarchical collapse (GHC). GHC constitutes a flow regime of (non-homologous) collapses within collapses, in which all scales accrete from their parent structures, and small, dense regions begin to contract at later times, but on shorter timescales than large, diffuse ones. The different timescales allow for most of the clouds' mass to be dispersed by the feedback from the first massive stars, maintaining the cloud-scale star formation rate (SFR) low.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 286 publications
(649 reference statements)
4
10
0
Order By: Relevance
“…There is evidence for delayed O star formation in the ONC (O'Dell et al 2009), W3 Main (Tieftrunk et al 1997;Feigelson, & Townsley 2008;Bik et al 2014), and M 17 SW (Povich et al 2016). This picture is consistent with the global hierarchical gravitational collapse by Vázquez-Semadeni et al (2019) who explain late massive star formation in the central potential well and later destruction of filamentary gas feeding by OB stellar feedback.…”
Section: Initial Mass Function Of Iras 09002-4732supporting
confidence: 89%
See 2 more Smart Citations
“…There is evidence for delayed O star formation in the ONC (O'Dell et al 2009), W3 Main (Tieftrunk et al 1997;Feigelson, & Townsley 2008;Bik et al 2014), and M 17 SW (Povich et al 2016). This picture is consistent with the global hierarchical gravitational collapse by Vázquez-Semadeni et al (2019) who explain late massive star formation in the central potential well and later destruction of filamentary gas feeding by OB stellar feedback.…”
Section: Initial Mass Function Of Iras 09002-4732supporting
confidence: 89%
“…More commonly, either the cluster is sparse (dozens of stars) or the rich cluster has already destroyed its natal molecular environment. The stellar spatial distribution, individual properties (ages, extinction) and collective properties (population, IMF, cluster structure) directly support contemporary numerical calculations of cluster formation in clouds that involve the hierarchical formation and merging of groups in molecular filaments such as those described by Vázquez-Semadeni et al (2019) and Krumholz et al (2019).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is also reported that the global collapse leads in a chaotic and hierarchical manner, yielding gravitationally driven fragmentation in star-forming molecular clouds (e.g., Burkert & Hartmann 2004;Heitsch et al 2009;Galván-Madrid et al 2009;Peretto et al 2013;Beuther et al 2015;Liu et al 2015Liu et al , 2016bFriesen et al 2016;Jin et al 2016;Hacar et al 2017;Csengeri et al 2017;Yuan et al 2018;Jackson et al 2019;Barnes et al 2019;Vázquez-Semadeni et al 2019). The modeling results based on the global hierarchical gravitational collapse in molecular clouds by Vázquez-Semadeni et al (2019) indicate late birth of massive OB-stars and later loss of molecular gas feeding by feedback of massive stars. It also suggests that after the onset of global collapse, one can expect local collapse events in molecular clouds.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been suggested that star-forming clouds seem to be in a state of global gravitational contraction (e.g., Hartmann et al 2012;Vázquez-Semadeni et al 2019). It is also reported that the global collapse leads in a chaotic and hierarchical manner, yielding gravitationally driven fragmentation in star-forming molecular clouds (e.g., Burkert & Hartmann 2004;Heitsch et al 2009;Galván-Madrid et al 2009;Peretto et al 2013;Beuther et al 2015;Liu et al 2015Liu et al , 2016bFriesen et al 2016;Jin et al 2016;Hacar et al 2017;Csengeri et al 2017;Yuan et al 2018;Jackson et al 2019;Barnes et al 2019;Vázquez-Semadeni et al 2019). The modeling results based on the global hierarchical gravitational collapse in molecular clouds by Vázquez-Semadeni et al (2019) indicate late birth of massive OB-stars and later loss of molecular gas feeding by feedback of massive stars.…”
Section: Discussionmentioning
confidence: 99%